1994
DOI: 10.1177/00220345940730010701
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the β-adrenoceptor Antagonists Atenolol and Propranolol on Human Parotid and Submandibular-Sublingual Salivary Secretion

Abstract: The aim of the study was to evaluate the effects of a beta 1-selective (atenolol 50 mg q.d.) and a non-selective (propranolol 80 mg b.i.d.) beta-adrenoceptor antagonists on human stimulated parotid and submandibular-sublingual (SM-SL) gland secretion. A randomized double-blind, placebo-controlled cross-over ("Latin square") design was used in 19 healthy male volunteers. Stimulated parotid and SM-SL saliva were sampled immediately before and 7 days after the start of each treatment period. Stimulation of saliva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
1
3

Year Published

1995
1995
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 29 publications
4
20
1
3
Order By: Relevance
“…Moreover, propranolol treatment had no effects on stimulated parotid and submandibular fl ow rates but was associated with a trend towards reduced protein concentrations in the stimulated saliva samples [Watson et al, 1990]. Similar effects on salivary fl ow rates and protein levels by ␤ -adrenergic receptor blockade have been reported in human studies [Mandel and Katz, 1968;Nederfors et al, 1994]. There are undoubtedly multiple, complex and redundant interactions between salivary constituents, bacteria and the hard surfaces that function to protect against caries.…”
Section: Discussionsupporting
confidence: 53%
“…Moreover, propranolol treatment had no effects on stimulated parotid and submandibular fl ow rates but was associated with a trend towards reduced protein concentrations in the stimulated saliva samples [Watson et al, 1990]. Similar effects on salivary fl ow rates and protein levels by ␤ -adrenergic receptor blockade have been reported in human studies [Mandel and Katz, 1968;Nederfors et al, 1994]. There are undoubtedly multiple, complex and redundant interactions between salivary constituents, bacteria and the hard surfaces that function to protect against caries.…”
Section: Discussionsupporting
confidence: 53%
“…One approach focuses on persons taking medications that directly affect salivary protein secretion and synthesis. Experiments with human volunteers have shown that beta-adrenergic antagonists selectively reduce secretion of acinar cell products, including amylase, peroxidase, histatins, and statherin (Laurikainen et al, 1988;lensen et al, 1994;Nederfors et al, 1994). Similar alterations have been seen in asthmatics medicated with beta-adrenergic agonists, possibly due to receptor down-regulation (Ryberg et al, 1987).…”
Section: (B) Longitudinal Studiesmentioning
confidence: 94%
“…Medication may be the most significant source of salivary changes in older adults. Anti-cholinergic sideeffects of antihistamines or anti-depressives may induce xerostomia (Spak et al, 1994), while beta-adrenergic agonists or antagonists may alter the concentrations of proteins secreted by acinar cells (Ryberg et al, 1987;Laurikainen et al, 1988;Nederfors et al, 1994). Medication effects need to be controlled when salivary proteins are studied in relation to oral disease in elderly populations.…”
Section: (D) Long-term Changementioning
confidence: 99%
“…Given these observations, adrenergic agonists and antagonists may change sAA activity due to their impact on adrenoceptor mediated protein secretion (Garrett, 1987;Proctor and Shori, 1996;Busch and Borda, 2000) and salivary flow rate (Parvinen et al, 1984). Up to date, only two studies investigated the effects of regular AD consumption on basal sAA activity and showed a diminishing effect on sAA activity (Nederfors et al, 1994;Nederfors and Dahlöf, 1996). However, samples were collected only once per assessment time point.…”
Section: Introductionmentioning
confidence: 99%